Komposisi ikan karang di lokasi transplantasi karang di Pulau Rubiah, Kota Sabang, Aceh - Nur Fadli; Aidia N; Muhammad M; Edi Rudi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract-. Coral transplantation is one of the techniques to rehabilitate the damaged coral reefs. The objective of this study is to observe the composition of reef fishes in the coral transplantation location in Rubiah Island, Sabang. The study was conducted in February 2011. Some of reef fishes Family were found in coral transplantation location (16 Family at 3 meters and 14 Family at 10 meters). The Family of Acanthuridae, Chaetodontidae, Pomacentridae Scaridae and Labridae were found in 3 meters. Reef fish families that dominated at depths of 10 meters were the Family of Acanthuridae, Pomacentridae Scaridae and Chaetodontidae. There are 40 reef fish species found in this study (34 species in 3 m and 38 species in 10m). Some reef fishes that were found in the transplantation area suggested that coral reefs rehabilitated using the technique of transplantation can improve its function as habitat for reef fish.Keywords: Transplantation, coral reefs, Rubiah Island